2009
DOI: 10.1021/ma9002853
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Nanocomposites of Polypropylene with Layered Silicates

Abstract: The melt rheological properties of layered silicate nanocomposites with maleic anhydride (MA) functionalized polypropylene are contrasted to those based on ammonium-terminated polypropylene. While the MA functionalized PP based nanocomposites exhibit solid-like linear viscoelastic behavior, consistent with the formation of a long-lived percolated nanoparticle network, the single-end ammonium functionalized PP based nanocomposites demonstrated liquid-like behavior at comparable montmorillonite concentrations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…The concept of creating both structural and functional multi-nanophase composites with improved performance is currently under development in a wide variety of metallic, ceramic and polymeric matrices, although the emphasis to date has been on polymeric systems [1][2][3]. By introducing carbon nanotubes (CNT) into a polymer matrix, many properties can be improved at once, including mechanical [4,5], thermo-mechanical [6], electrical [7,8], thermal [9,10], chemical [11] and optical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of creating both structural and functional multi-nanophase composites with improved performance is currently under development in a wide variety of metallic, ceramic and polymeric matrices, although the emphasis to date has been on polymeric systems [1][2][3]. By introducing carbon nanotubes (CNT) into a polymer matrix, many properties can be improved at once, including mechanical [4,5], thermo-mechanical [6], electrical [7,8], thermal [9,10], chemical [11] and optical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…A tiny fluctuation of Tg was exhibited among the epoxy-nanocomposites with different content of LVHS-OMMT in Fig.13. It has been reported that the addition of the organoclay can increase Tg by strengthening the polymer network by the polymer absorbed on the surface of the filler (increase of entanglements) [19][20] , while the free flexible silicone macromolecules can decrease it. These two factors, which provide the opposite effect, may account for the tiny fluctuation in Tg.…”
Section: Dma Analysis Of Epoxy-nanocompositesmentioning
confidence: 99%
“…Hence, polymer/layered silicate nanocomposites have been attracting intense interest in recent years [11][12][13][14][15]. As a type of regularly interstratified clay mineral, rectorite (REC) is made of alternative dioctahedral mica-like layer and dioctahedral smectite-like layer at a 1:1 ratio.…”
Section: Introductionmentioning
confidence: 99%